2010
DOI: 10.1016/j.jmr.2010.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Multi-compound polarization by DNP allows simultaneous assessment of multiple enzymatic activities in vivo

Abstract: Methods for the simultaneous polarization of multiple 13 C-enriched metabolites were developed to probe several enzymatic pathways and other physiologic properties in vivo, using a single intravenous bolus. A new method for polarization of 13 C sodium bicarbonate suitable for use in patients was developed, and the co-polarization of 13 C sodium bicarbonate and [1-13 C]pyruvate in the same sample was achieved, resulting in high solution state polarizations (15.7% and 17.6%, respectively) and long spin-lattice r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
186
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 163 publications
(191 citation statements)
references
References 24 publications
4
186
0
1
Order By: Relevance
“…The principal advantage of hyperpolarized 13 C MRI over other molecular imaging modalities is detection of 13 C metabolites by chemical shift, allowing real-time evaluation of physiologically relevant enzyme fluxes in vivo. Data obtained are potentially confounded by differential perfusion of (and transport into) tissues of interest, a problem that has been addressed by copolarization of 13 C probes with a perfusion agent, for example the intravascular agent 13 C urea (36). As for prior studies employing [1-13 C] pyruvate, we found for [1-13 C] DHA that the observed total 13 C signal (VitCþ DHA) was highest in tissues that are well perfused, including brain, liver, kidneys, and tumor.…”
Section: Discussionmentioning
confidence: 99%
“…The principal advantage of hyperpolarized 13 C MRI over other molecular imaging modalities is detection of 13 C metabolites by chemical shift, allowing real-time evaluation of physiologically relevant enzyme fluxes in vivo. Data obtained are potentially confounded by differential perfusion of (and transport into) tissues of interest, a problem that has been addressed by copolarization of 13 C probes with a perfusion agent, for example the intravascular agent 13 C urea (36). As for prior studies employing [1-13 C] pyruvate, we found for [1-13 C] DHA that the observed total 13 C signal (VitCþ DHA) was highest in tissues that are well perfused, including brain, liver, kidneys, and tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Exchange of hyperpolarized 13 C label between [1-13 C]pyruvate and endogenous lactate was analyzed using a simple two-site exchange model (8), to give the first order rate constant describing flux of label between pyruvate and lactate (k P ) and the relaxation rate constant for both species (R 1 ). In experiments with [1][2][3][4][5][6][7][8][9][10][11][12][13] C]lactate, there is minimal exchange of label with the small endogenous pyruvate pool (17) and therefore R 1 for lactate was estimated directly from its apparently monoexponential signal decay.…”
Section: Discussionmentioning
confidence: 99%
“…For studies of the effect of MCT inhibition on the echo/FID ratio following injection of [1][2][3][4][5][6][7][8][9][10][11][12][13] C]lactate (n ¼ 25), data were acquired using a surface coil and the S180 pulse sequence with an echo time of 310 ms. These acquisition conditions match those used in the heteronuclear spin-echo experiment described in our previous study with L-[U-2 H,1-…”
Section: Mr Spectroscopy In Vivomentioning
confidence: 99%
See 2 more Smart Citations